Pengaruh Budaya Organisasi Dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Kantor Badan Pusat Statistik Kota Padang - Regita Syafitri; Vicky Brama Kumbara; Desi Permata Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
Regita Syafitri, 22101155310268, Management Department, 2022, The Influence of Organizational Culture and Transformational Leadership on Employee Performance with Job Satisfaction as an Intervening Variable at the Padang City Central Statistics Agency Office, under the guidance of Mr. Dr. Vicky Brama Kumbara, S.E., M.M and Mrs. Dr. Desi Permata Sari, S.E., M.M. This study aims to determine and try to analyze the Influence of Organizational Culture and Transformational Leadership on Employee Performance with Job Satisfaction as an Intervening Variable at the Padang City Central Statistics Agency Office. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of the Padang City Central Statistics Agency Office. The research results found a significant influence between organizational culture and job satisfaction. There was a significant influence between transformational leadership and job satisfaction. There was a significant influence between organizational culture and employee performance. There was a significant influence between transformational leadership and employee performance. There was a significant influence between job satisfaction and employee performance. Job satisfaction mediated the influence of organizational culture on employee performance. Job satisfaction mediated the influence of transformational leadership on employee performance.